Environmental, social and governance and the efficiency of government-linked companies in Malaysia - Kweh Q.L.; Alrazi B.; Chan Y.C.; Abdullah W.M.T.W.; Lee R.M.A. (Faculty of Economics and Administration, 2023)
Environmental, social and governance (ESG) are non-financial performance indicators that help determine financial performance. This study, motivated by the increasing awareness of various stakeholders about the importance of ESG disclosure, explores the impacts of ESG on firm efficiency of government-linked companies (GLCs) in Malaysia from 2006 to 2012. The ESG disclosure is based on the Sustainalytics ESG Research data available in Bloomberg while data development analysis (DEA) is used to estimate firm efficiency. This study found that GLCs focused more on governance disclosures, followed by social and environmental aspects. Governance improved firm efficiency, but social and environmental factors had no similar effects. In conclusion, this study provided insight on ESG initiatives which are useful for stakeholders when making financial and investment decisions. 2017 Institutions and Economies All rights reserved.